Interferensi Morfologi dan Sintaksis Bahasa Indonesia Terhadap Bahasa Jepang Pada Pembuatan Kalimat Pasif Bahasa Jepang oleh Pembelajar Bahasa Jepang - Delia Budi Kamila; Eka Marthanty Indah Lestari (Universitas Negeri Semarang, 2022)
This study aims to explain the forms of morphological and syntactic interference of the Indonesian language in Japanese language learners' production of Japanese passive sentences. The data were then analyzed as errors because of the two interference. Research data was obtained through an open questionnaire distributed to Japanese Literature Study Program students during the 4th semester at Brawijaya University. Based on the research, the total forms of morphological interference found were 47. Morphological interference in the transfer of morphemes was the most common, namely 42 or 89%, followed by the removal of grammatical categories, as much as 4 or 9% and the most diminutive replicas of grammatical functions, as much as 1 or 2%.Meanwhile, syntactic interference is 33. The number of syntactic interference in phrase patterns is 22 or 69%, and syntactic interference in sentence patterns is 11 or 31%. Based on the data on the findings of morphological and syntactic interference in the Indonesian language, the form of errors following Parera's (1997) theory is 55. The number of 52 or 94% production errors is the highest, followed by a decrease of 2 or 4%; and the least is overproduction of 1 or 2%. Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalJapanese MorphologyJapanese SyntaxJapanese Passive VoiceJapanese Language Education